THE EFFECT OF SELF-EFFICACY ON DATA LITERACY SKILLS AMONG JUNIOR HIGH SCHOOL STUDENTS IN THE ULU SOSA SUBDISTRICT - Yulia Nasution; Suci Dahlya Narpila (FKIP Universitas Muhammadiyah Tangerang, 2026)
Data literacy is an essential competency that students need to develop in order to deal with the increasing amount of information in the digital era. However, students' data literacy skills remain relatively low. One factor that is believed to influence these skills is self-efficacy, which refers to an individual's belief in their ability to accomplish specific tasks. This study aimed to examine the effect of self-efficacy on the data literacy skills of junior high school students in Ulu Sosa District. The study employed a quantitative approach using an ex post facto research design. The sample consisted of 30 eighth-grade students selected through cluster random sampling. Data were collected using a self-efficacy questionnaire and a data literacy test and were analyzed using descriptive statistics and simple linear regression. The results indicated that self-efficacy had a positive and significant effect on students' data literacy skills, with the regression equation Y = 23.339 + 1.488X and a significance value of p < 0.05. The coefficient of determination (R² = 0.948) showed that self-efficacy contributed 94.8% to students' data literacy skills, while the remaining 5.2% was influence